To life! : a celebration of Jewish being and thinking - Kushner, Harold S. (Boston : Little, Brown, 1993)
Author's writings on the practices and traditions of Judaism.
Life is the question, Judaism is the answer -- The stories we tell about ourselves -- The sacred deed--making the ordinary extraordinary -- Sanctuaries in time : the calendar -- What we believe about God -- What we believe about people -- When we pray -- Personal milestones -- Why we love Israel -- Why do some people hate us? -- Jews and Christians in today's world -- Why you need to be a Jew.
Keywords: Judaism; Jewish way of life